A Stacked Multi-Sensor Platform for Real-Time MRI Guided Interventions. (February 2023) - Zolfaghari, Parviz; Erden, Oguz K.; Tumer, Murat; Yalcinkaya, Arda D.; Ferhanoglu, Onur
Highlights: We present a MEMS sensor readout glasses pair for monitoring Intraocular pressure. The proposed device can operate under ± 8 degrees of eye tilt. A reference grating is used to cancel out intensity deviations due to external factors. 40 mmHg pressure range is demonstrated with near 4 nm/mmHg displacement sensitivity Abstract: We present a stacked temperature, pressure, and localization platform, targeted for minimally invasive surgical and diagnostic applications under Magnetic Resonance Imaging. The platform comprises a micro-fabricated three-layer (Titanium-Parylene-Titanium) membrane pressure sensor, a Gallium Arsenide band-gap temperature sensor, and a magnetic material on double prism retro-reflector that benefits from Magneto-Optic Kerr effect as a magnetic field sensor, to provide localization feedback under Magnetic Resonance Imaging. All sensors can be addressed with a single fiber optic cable, where the collected light is directed to a spectrometer and a polarimeter. For the three-layer microfabricated membrane sensor, an analytical formulation is derived, linking the pressure to optical intensity. Moreover, finite-element simulation results are provided, verifying analytical findings. Wavelength division multiplexing is exploited to address the sensors simultaneously. We measured sensitivities of 0.025 millidegree/Gauss rotation of polarization, 1.5 nm/mmHg displacement (in agreement with simulation results and analytical findings), 0.36 nm/ ° C bandgap wavelength shift for magnetic field, pressure, and temperature sensors; respectively. With further development, the proposed device can be adapted to a clinical setting for use in Magnetic Resonance assisted surgical procedures.